MODUS DAN FAKTOR PENYEBAB MARAKNYA KASUS PEKERJA MIGRAN INDONESIA (PMI) ILEGAL DI KABUPATEN LUMAJANG - Fathullah, Kholidazia El Hamzah; Ma’shum, Ahmad Djazim (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
Abstract The low level of wages in the country is related to the limited number of jobs available, making people prefer to work abroad. Most Indonesian Migrant Workers (PMI) choose illegal routes. In many cases of illegal migration, both in the context of internal migration and international migration, the role of